THE RESIDUAL EFFECT OF LIQUID POULTRY MANURE ON THE GROWTH AND N, P, K CONTENT OF MAIZE CROP - Ali İnal; A.reşit Brohi; M.rüştü Karaman (Journal of Agricultural Sciences)
The main object of this study is to evaluate liquid poultry -manure as a fertilizer to solve the problem of the farm and environment and also to see the residual effect of liquid poultry manure on the yield and N-PK content of maize crop, tobacco-waste and farm yard manure treatments were also included in this experiment for comparison. The experiment was laid out on completely randomized design with 10 treatments and 3 replications in greenhouse conditions. Pots containing 4 kg of air dried soil was used. Liquid poultry manure at the rates of O, 1.5, 3.0, 4.5, 6.0, 7.5 t/da on dry basis were applied at band, whereas tobacco waste at the rates of 3 and 4 t/da and farm yard manure at the rates of 2.5 and 5.0 t/da were mixed with soil and kept at field capacity for one month Cumhuriyet wheat variety was sown and harvested 9 weeks after sowing. After harvesting wheat plants, H-2274 maize variety was sown in the same pots and grown for 8 weeks to study the residual effect of organic fertilizers used in this research. According to the results of this experiment, increasing rates of liquid poultry manure LPM , tobacco-waste TW and farm yard manure FYM significantly increased the dry matter yield DMY and N,P,K uptake of maize crop than that of control plants. Maximum DMY 20.50 g/pot was obtained with 4.5 t/da rate of LPM, while dry matter yield of control plants was 3.67 g/pot.